Relationship of Thermal Treatment and Antioxidant Capacity in Cooked Foods - Navajas Porras, Beatriz; Pérez-Burillo, Sergio; Hinojosa-Nogueira, Daniel; Pastoriza, Silvia; Rufián-Henares, José Ángel (MDPI, 2022)
Most of the foods we eat undergo a cooking process before they are eaten. During such a process, the non-enzymatic browning occurs, which generates compounds such as furosine, 5-hydroxymethylfurfural (HMF) and furfural. These are considered markers of cookedness and can therefore be used as quality indicators. In this work, we study the production of these compounds in different foods (both of plant and animal origin) that are cooked with different techniques. Additionally, we investigate correlations between the production of these markers of cookedness and the antioxidant capacity produced after in vitro digestion and fermentation. We observe that, in general, cereals and vegetables are more thermally damaged. Toasting and frying produce the highest concentrations of Maillard compounds whereas boiling the lowest. Furosine content shows a significant positive correlation with in vitro digestion data in fried foods, and with fermentation in roasted foods. Furfural content shows a significant positive correlation with in vitro digestion results in roasted foods, specifically in the Folin–Ciocalteu method.
Keywords: Maillard, Reacción de; Alimentos - Manipulación; Maillard reaction; Furosine; Furfural; Cooking; Antioxidant activity